2022
DOI: 10.1002/jsfa.12315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potential allelochemicals in a water extract of Abutilon theophrasti Medik. on germination and growth of Glycine max L., Triticum aestivum L., and Zea mays L

Abstract: BACKGROUND Velvetleaf (Abutilon theophrasti Medik.), primarily a cropland weed, exerts adverse impacts on the productivity of various crops, including soybean (Glycine max L.), wheat (Triticum aestivum L.), and maize (Zea mays L.), by hindering their vegetative growth. However, the interference mechanism of velvetleaf on the three crops remains unclear. RESULTS The inhibitory effect of velvetleaf water extract on the germination and growth of soybean, wheat, and maize was determined in pot experiments and fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This connotes that the microbes in termite mound soil can produce allelochemical phenolic—a chemical that affects metabolic processes, stimulate plant root growth, and promote seed germination. 35 Genes that help in iron acquisition and metabolism were reported from this study (Figure 6). These genes enable microorganisms to utilize iron for stimulating metabolic enzymes/pathways.…”
Section: Discussionmentioning
confidence: 66%
“…This connotes that the microbes in termite mound soil can produce allelochemical phenolic—a chemical that affects metabolic processes, stimulate plant root growth, and promote seed germination. 35 Genes that help in iron acquisition and metabolism were reported from this study (Figure 6). These genes enable microorganisms to utilize iron for stimulating metabolic enzymes/pathways.…”
Section: Discussionmentioning
confidence: 66%
“…It is also known that the amount and variety of allelochemicals in the leaves of grasses are high, which may have an inhibitory effect on the germination and growth of other plants [31]. The study conducted by Shi et al (2023) showed that the aqueous extract of Abutilon theophrasti leaves at high concentrations had an inhibitory effect on the germination and growth of Glycine max L., Triticum aestivum L., Zea mays [32]. In another study on the allelopathic effects of aqueous leaf extracts of two grass species, Urochloa decumbens and Urochloa ruziziensis, it was shown that they had inhibitory effects on the weeds Chloris ventricosa, Bidens pilosa, Commelina benghalensis L., Conyza canadensis, and Digitaria insularis and caused a decrease in the percentage of germination, root growth, shoot growth, and biomass of the weeds [33].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that different grass genotypes have different inhibitory effects on the growth of E. sativa L. (Figure 1, Table 4), such that the highest growth reduction was caused by the genotypes of Festulolium species including GR 1692, GR 5004, and GR 5009 (Figure 1, Table 4). The different allelopathic effects of plants on the target species may be due to the presence of different levels of allelochemicals in plants, which is caused by the different abilities of plants to synthesize allelopathic substances [32,45]. Previous studies have shown that there is variation among different grass species in their ability to suppress weeds, and the allelopathic effect varies among different species and genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the contents of soil pH, soil organic matter, total nitrogen, total phosphorus, ammonium nitrogen, nitrate nitrogen, available phosphorus, total potassium, and available potassium vary with different concentrations of donor plant water extracts, which changes soil physical and chemical properties and soil quality, thus indirectly affecting the growth and development of recipient plants [33]. We tested the effects of different concentrations of F. carica root extracts on soil physicochemical properties (pH, EC, SOC, AN, AP, AK) of T. cuspidata.…”
Section: Effects Of F Carica Water Extract On Soil Properties Of T Cu...mentioning
confidence: 99%